Dandelion Root and Lemongrass Extracts Induce Apoptosis, Enhance Chemotherapeutic Efficacy, and Reduce Tumour Xenograft Growth In Vivo in Prostate Cancer. (17th July 2019) - Nguyen, Christopher; Mehaidli, Ali; Baskaran, Kiruthika; Grewal, Sahibjot; Pupulin, Alaina; Ruvinov, Ivan; Scaria, Benjamin; Parashar, Krishan; Vegh, Caleb; Pandey, Siyaram
Abstract : Many conventional chemotherapies have indicated side effects due to a lack of treatment specificity and are thus not suitable for long-term usage. Natural health products are well-tolerated and safe for consumption, and some have pharmaceutical uses particularly for their anticancer effects. We have previously reported the anticancer efficacy of dandelion ( Taraxacum officinale ) root and lemongrass ( Cymbopogon citratus ) extracts. However, their efficacy on prostate cancer and their interactions with standard chemotherapeutics have not been studied to determine if they will be suitable for adjuvant therapies. If successful, these extracts could potentially be used in conjunction with chemotherapeutics to minimize the risk of drug-related toxicity and enhance the efficacy of the treatment. We have demonstrated that both dandelion root extract (DRE) and lemongrass extract (LGE) exhibit selective anticancer activity. Importantly, DRE and LGE addition to the chemotherapeutics taxol and mitoxantrone was determined to enhance the induction of apoptosis when compared to individual chemotherapy treatment alone. Further, DRE and LGE were able to significantly reduce the tumour burden in prostate cancer xenograft models when administered orally, while also being well-tolerated. Thus, the implementation of these well-tolerated extracts in adjuvant therapies could be a selective and efficacious approach to prostate cancer treatment.